2002
DOI: 10.1111/j.1834-7819.2002.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Children with Gastro‐Esophageal Reflux Disease: A Controlled Study

Abstract: Background:The aim of this study was to compare the dental health of children with gastro-esophageal reflux disease (GERD) with a healthy control group. Methods: Dental examinations were conducted for 52 children (31 boys and 21 girls) with a definitive history of GERD. For every subject enrolled in the study, a healthy control sibling without the condition was recruited. Medical histories were obtained from medical records, and dental and dietary histories were obtained from parents. The teeth were examined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 27 publications
3
64
0
9
Order By: Relevance
“…Studies in Australia [9] and Turkey [8] that compared DE in children with GERD with a control group found that children with GERD had more dental erosion experience than did those without GERD. The present study did not aim to associate GERD with DE, because only children with GERD were examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Australia [9] and Turkey [8] that compared DE in children with GERD with a control group found that children with GERD had more dental erosion experience than did those without GERD. The present study did not aim to associate GERD with DE, because only children with GERD were examined.…”
Section: Discussionmentioning
confidence: 99%
“…However in a blinded study with children with and without symptoms of GER the proportion of teeth affected by DE was similar [10]. There is insufficient information in the literature evaluating the associated factors of DE in children with GERD [9]. The identification of the risk factors is increasingly important to establish preventive measures, especially in individuals with GERD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After histological and symptoms-based diagnosis of GERD, the difference between dental erosion in GERD patients compared with subjects of a control group showed statistical significance; although these lesions were found on permanent teeth only, increased caries frequency was also found. 12 Other studies showed a strong correlation between salivary pH, dental erosion incidence and caries frequency as well. 13,14 Besides GERD, many other factors can contribute to a low pH value; these are the so-called cariogenic factors such as bacteria, oral hygiene, diet, drugs.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although several studies have demonstrated that the extremely high acidity reduces bacterial growth, the mainly acidic oral environment in GERD may contribute to increased levels of acid-producing S. mutans bacteria, which will lead to increased caries frequency and other types of structural alterations of the enamel, such as dental erosion. 19 …”
Section: Discussionmentioning
confidence: 99%